Fluid Flow Analysis of Concentric Heat Exchanger with Different Nano Fluids and Mass Flow Rates (International Journal of Innovative Research in Engineering & Management, 2022)
In this article, the overall performance of  water and other nano fluids mixed with base fluid water in a  twin pipe warmth exchanger is investigated. At quantity  fractions of 0.35 percentage, the nano fluids are Silicon  Oxide and silver nano fluid. The traits of nano fluids are  decided the usage of theoretical calculations, which can be  then utilised as inputs for analysis. CATIA parametric  software program is used to create a 3D model of the dual  pipe heat exchanger (plain and coil insert tube). CFD  research of a dual pipe warmth exchanger with water,  silicon oxide, and silver nano particle at diverse mass float  fees of zero.32, zero. Fifty two, 0.72,zero.Ninety two, and  1.12 kg/sec is performed. Theoretical calculations on the  twin pipe warmness exchanger had been additionally  finished.
Keywords: CFD; NANO FLUID; CATIA